Strategic Expansion in the Construction Business: A Financial Feasibility Study of a New Fabrication Workshop - Hasbi, Muhaimin; Maya Damayanti, Sylviana (Journal Research of Social Science, Economics, and Management, 2026)
This study evaluates the financial feasibility of establishing a steel fabrication workshop for ZAN Construction, a design-and-build contractor in Bandung, and compares two candidate locations: Bekasi City and West Bandung Regency. The research addressed the firm’s dependence on third-party fabrication, which previously caused an estimated opportunity loss of IDR 793 million in a single bridge project. Using a single embedded case design, the study combines quantitative capital budgeting with qualitative strategic analysis. The quantitative model projects a ten-year investment for a workshop with an annual capacity of 1,200 tons, financed equally by debt and equity. The discount rate is calculated through CAPM and adjusted using the firm’s capital structure, producing a Weighted Average Cost of Capital of approximately 11.5%. Financial feasibility is assessed using Net Present Value, Internal Rate of Return, Profitability Index, and Payback Period.The results show that both locations are financially feasible. Bekasi City generates an NPV of approximately IDR 30.1 billion, an IRR of 25.9%, a PI of 2.04, and a discounted payback period of 5.8 years. West Bandung Regency performs better, with an NPV of IDR 33.6 billion, an IRR of 31.8%, a PI of 2.52, and a discounted payback period of 4.7 years. The stronger performance of West Bandung Regency is mainly driven by lower land and labor costs, while both locations use the same revenue and utilization assumptions. Sensitivity analysis identifies raw steel price as the most critical variable, followed by production volume and labor cost.